AGE AND PREGNANCY DISTANCE AS A RISK FACTOR FOR ANEMIA CAUSES IN PREGNANT MOTHERS IN THE AREA OF PUBLIC HEALTH CENTRE OF BANJARNEGARA REGENCY - Dewie Sulistyorini; Ratih Subekti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Anemia is a condition where the body has a few numbers of red blood cells (erythrocytes). This condition is commonly found in pregnant women. WHO determines the incidence of anemia in pregnancy ranging from 20% to 89% by determining Hb less than 11 gr%. The purpose of this study was to determine the age and distance of pregnancy in pregnant women with anemia in the public health centre in Banjarnegara. The method used in this study was descriptive analysis. Sampling-based on total sampling, amounting to 29 people. The results showed that most of the